Solution combustion method to synthesize magnetic Fe3O4 as photocatalytic of Congo red dye and antibacterial activity. Issue 1 (November 2021) - Salni,; Said, M; Hariani, P L; Apriani, I
Abstract: Fe3 O4 has been synthesized using the combustion solution method using glycine as fuel. The Fe3 O4 was used as a catalyst in the photocatalytic degradation of Congo red dye. The Fe3 O4 were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS), UV-Vis spectroscopy, and vibrating sample magnetometry (VSM). The characterization showed that Fe3 O4 has an inverse spinel structure with a crystalline size of 35.6 nm. Fe3 O4 has an optical band gap of 2.16 eV, and a saturation magnetization of 83.76 emu/g. The study showed that the highest photocatalytic degradation was at 90 min of irradiation time using visible light irradiation, the concentration of Congo red dye of 10 mg/L, and pH solution of 5, with a photocatalytic degradation efficiency of 97.70%. The experiment indicated that the photocatalytic degradation of the Congo red dye by Fe3 O4 followed a pseudo-first-order. Fe3 O4 is effective as an antibacterial against gram-positive bacteria ( Streptococcus aureus ) and gram-negative bacteria ( Escherichia coli ).